Analisis Kelayakan dan Pemilihan Investasi Alat Gali-Muat dan Alat Angkut di PT. Bara Prima Pratama Blok Retih Desa Batu Ampar Kecamatan Kemuning Kabupaten Indragiri Hilir Provinsi Riau - Fadel Muhammad; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Bara Prima Pratama is a coal mining company located in Riau Province. The company has a production operation IUP on the Retih block with an estimated reserve of 2,635,406 tons of coal with a stripping ratio is 1:15.6 and a planned production target is 527.081 tons/year. The purpose of this research is to determine the investment feasibility of loading equipment and hauling equipment for decisioning as well as the most profitable alternative for the company to purchase it. The results of the feasibility analysis of the investment in digging and hauling equipment using the NPV and IRR methods for each alternative, there are some feasible and unfeasible alternative were obtained. Based on the Net Present Value (NPV) method, investments by cash and leasing are feasible with an NPV is Rp.28,361,887,549 for cash and NPV is Rp.10,428,627,129 for leasing, while the rent is not feasible because the NPV < 0, it is - Rp. 13,855,255,703. Based on the Internal Rate of Return (IRR) method with a MARR is 9.23%, investments by cash alternative are only feasible with an IRR value is 41.29%, while leasing and rent are unfeasible because the value of IRR < MARR , IRR value is -21.7% for leasing alterative and IRR value is -11.22% for rent alternative. So, based on the results of the analysis for the best alternative according to the NPV and IRR methods, the most profitable for the company is cash alternative.